Fractal dimension analysis: A new tool for analyzing colony-forming units - Nai, Gisele Alborghetti; Martelli, Cesar Alberto TALAvera; Medina, Denis Aloísio Lopes; Oliveira, Mayla Silva Cayres de; Caldeira, Isadora Delfino; Henriques, Bruno Carvalho; Portelinha, Maria Júlia Schadeck; Eller, Lizziane Kretli Winkelstroter; Marques, Mariângela Esther Alencar [UNESP] (Elsevier, 2021)
The gold standard for quantifying bacteria both in routine diagnostics and in research is plating followed by count of colony-forming units (CFU). But, manual CFU counting on plates is time-consuming and subjective. We evaluated fractal dimension as a new methodology for evaluating CFU. Twenty fragments of expanded polytetrafluoroethylene (ePTFE) synthetic vascular prosthesis and 20 silicone prostheses were embedded in bacterial suspensions and incubated. The prostheses were then sown in solid culture medium and incubated for 48 h. Petri dishes were photographed and analyzed by fractal dimension. There was correlation between the number of CFU in manual counting and the fractal dimension analysis (p = 0.0001). We demonstrated that fractal dimension is a useful method for microbiological analyses in researches. It makes CFU analysis easier and faster and can be used regardless of the culture medium. • Petri dishes with different bacterial colonies were photographed with a digital camera under natural light. • The images were binarized and analyzed with ImageJⓇ's “fractal dimension” tool. • Fractal dimension analysis showed to be a good tool for evaluating the amount of colony-forming unit.
Keywords: Colony-forming units counting (CFU); Computer-assisted; Image processing; Microbial colony count; Prostheses and implants